Rios Ventures of Hoffman Estates, Illinois - Thompson, Kenneth R. (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Being an entrepreneur is a challenge; being an immigrant and an entrepreneur poses additional challenges. This case starts with a view of what several entrepreneurs and venture capitalists agree are some of the key elements of what it takes to start a business. Students then have the opportunity to analyze how these key elements apply to the experience of Eugene Rios, an immigrant entrepreneur who started his own trucking company while working at a catering business.Eugene Rios came up with an idea that would save the catering company money and, at the same time, would help him to start his own business. This is a story of the ideas and drive of an immigrant entrepreneur who had an idea that could reduce costs for his employer and allowed him to use his connections in his community to keep his trucks working during the slack season of the catering company.While the pandemic created severe challenges, the catering company still provided support to keep the trucking company in business, creating greater employee loyalty and a win-win situation for both organizations.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Immigrant business enterprises -- Case studies; Employee loyalty -- Case studies